2009
DOI: 10.1002/jrs.2265
|View full text |Cite
|
Sign up to set email alerts
|

FT‐IR, FT‐Raman and DFT calculations of the salicylanilide derivate 4‐chloro‐2‐(4‐bromophenylcarbamoyl)phenyl acetate

Abstract: FT-IR and FT-Raman spectra of 4-chloro-2-(4-bromophenylcarbamoyl)phenyl acetate were recorded and analyzed. The vibrational wavenumbers and corresponding vibrational assignments were examined theoretically using the Gaussian03 set of quantum chemistry codes. The red shift of the NH stretching wavenumber in the infrared (IR) spectrum from the computed wavenumber indicates the weakening of the NH bond resulting in proton transfer to the neighbouring oxygen atom. The simultaneous IR and Raman activations of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
4
10
0
Order By: Relevance
“…The calculated first hyperpolarizability of the title compound is 4.559 × 10 −30 esu, which is comparable with the reported values of similar derivatives, [97] but the experimental value is not readily available. We conclude that the title compound is an attractive object for future studies of nonlinear optical properties.…”
Section: Geometrical Parameters and Hyperpolarizabilitysupporting
confidence: 77%
“…The calculated first hyperpolarizability of the title compound is 4.559 × 10 −30 esu, which is comparable with the reported values of similar derivatives, [97] but the experimental value is not readily available. We conclude that the title compound is an attractive object for future studies of nonlinear optical properties.…”
Section: Geometrical Parameters and Hyperpolarizabilitysupporting
confidence: 77%
“…The calculated first hyperpolarizability of the title compound is 4.101 × 10 −30 esu, which is comparable with the reported values of similar derivatives, [71] but experimental evaluation of this data is not readily available. We conclude that the title compound is an attractive object for future studies of nonlinear optical properties.…”
Section: Geometrical Parameters and First Hyperpolarizabilitysupporting
confidence: 76%
“…The IR bands in the 2880-1936 cm −1 region and their broadening support intramolecular hydrogen bonding. [32] Geometrical parameters and first hyperpolarizability…”
Section: Phenyl Ring Vibrationsmentioning
confidence: 99%
“…This work is a part of our investigations of substituted salicylanilide derivatives. The authors have reported the spectroscopic studies of 4-chloro-2-(4-bromophenylcarbamoyl)phenyl acetate [32] and 4-chloro-2-(3,4-dichloro phenyl carbamoyl) phenyl acetate. [33] To our knowledge, no theoretical HF or DFT calculations, or detailed vibrational IR and Raman analyses, have been performed on the title compound.…”
Section: Introductionmentioning
confidence: 99%